2000
DOI: 10.1046/j.1523-1747.2000.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Isolated from Positive Epicutaneous Test Reactions to Amoxicillin and Ceftriaxone are Drug Specific and Cytotoxic

Abstract: In order to investigate the function of T cells in cutaneous adverse drug reactions, skin-derived T cells were analyzed in two patients with a drug-induced exanthem. Skin biopsy specimens were obtained from positive epicutaneous test reactions to amoxicillin and ceftriaxone. Immunohistochemical analysis revealed that the majority of the cell infiltrate in both biopsy specimens was composed of activated T cells, of which some expressed perforin. By limiting dilution 36 amoxicillin-specific and 10 ceftriaxone-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 23 publications
4
50
0
1
Order By: Relevance
“…Identification of drug-specific T cells in the peripheral circulation and skin, at the time of the reaction, provides evidence that the immune system is involved in the development of clinical symptoms (Mauri-Hellweg et al, 1995;Schnyder et al, 1997;Yawalkar et al, 2000). Despite this, the nature of the drug antigen that stimulates hypersensitivity reactions is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of drug-specific T cells in the peripheral circulation and skin, at the time of the reaction, provides evidence that the immune system is involved in the development of clinical symptoms (Mauri-Hellweg et al, 1995;Schnyder et al, 1997;Yawalkar et al, 2000). Despite this, the nature of the drug antigen that stimulates hypersensitivity reactions is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Some 5-mm punch-biopsy specimens were obtained after 48 hours from the positive epicutaneous test reactions of patients AP, JS, and EB (Table 1). Drugspecific T cells were isolated and cloned as described previously in detail (31). The isolated cells were cultured in U-bottom 96-well plates in a final volume of 100 ”l/well with 2.5 × 10 4 allogeneic irradiated PBMCs in CM enriched with 1 ”g/ml PHA and 20 U/ml rIL-2 and expanded as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Of particular importance is the finding that elution of T cells from patch test lesions from two patients with bullous reactions to b-lactams revealed that about onethird of the infiltrating T cells were drug specific (52).…”
Section: Skin Testsmentioning
confidence: 96%